Improving soil organic nitrogen and sulfur pools by cover cropping and crop fertilization in soybean-based cropping systems - Crespo, Cecilia (2021)
Nitrogen (N) and sulfur (S) define crops productivity, and are currently deficient in most agricultural soils. In agricultural systems, management practices can affect N and S organic pools (Norg and Sorg, respectively). The objective of our study was to assess how intensification practices [use of grasses as cover crops (CC) and/or fertilization] affect Norg and Sorg, anaerobic N (Nan), and carbon (C)/N and C/S ratios as compared with soybean [Glycine max (L.) Merr.]monoculture, in soils under no tillage, with contrasting edaphoclimatic conditions. The experiment was carried out in four long term experiments (> 10 yr), where four treatments were evaluated: control (soybean monoculture (Sb)), soybean monoculture fertilized with phosphorus (P) and S (Sbf), CC / soybean (Sb/CC), and CC / P + S-fertilized soybean (Sbf/CC). The inclusion of CC increased Norg and Sorg as compared to Sb (from 20 % to 30 % for Norg, and from 16 % to 18 % for Sorg) at 0−5 cm.The magnitude of the effect of CC increase on Norg was positively associated with temperature, clay + silt and crops dry matter, whereas the increase in Sorg was positively associated with precipitation, clay + silt, and crops dry matter. The Nan improved over 50 % due to the inclusion of CC. Also, at two sites P + S-fertilization improved Nan (37 %) as compared with Sb. Our results suggest that intensification practices (CC and PS-fertilization) result in an accumulation of readily available N and S organic fractions, which can have a potential positive impact on the productivity of other crops in the cropping sequence. However, as previously mentioned, the magnitude of that positive effect will depend on the edaphoclimatic characteristics of each site.